Three-Phase Space Vector Pulse Width Modulation with Proportional Integral Derivative Control for High-Capacity Battery Charging - Nursandi, Elvin; Harahap, Charles Ronald; Setyawan, Fx Arinto (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2025)
The growing consumption electricity has burdened the existing power grid, potentially leading to overloads and power outages when supply does not meet demand. Integrating alternative resources, such as Gas Power Plants (PLTG), as backup solutions can mitigate these risks. PLTG relies on various DC components to power the machines, all supplied by a high-capacity battery bank. This research is conducted at the PLTG UPK Sebalang, where the existing system cannot stabilize the rectifier voltage during battery charging. As a result, failures occur during the generator starting process. Therefore, this study aims to stabilize the output voltage of the existing three-phase rectifier system at PLTG UPK Sebalang. To achieve this goal, the Space Vector Pulse Width Modulation (SVPWM) rectifier with Proportional Integral Derivative (PID) control method is proposed. This method dynamically reduces steady-state error to produce a stable output voltage from the rectifier. In repetitive experiments, the system effectively kept the rectifier voltage stable at 125V, experiencing an average decrease of just 1.05%.